In search of lost social cohesion in Bosnia and Herzegovina - Sarina Bakić, (Technium Social Sciences Journal, 2020)
Strengthening social cohesion draws not merely on social and economic rights but it is connected to all prerogatives relevant for enlarging the choices of individuals to live meaningful and decent life. Author’s attempt in this article is to analyse some of the substantial elements for social cohesion in general and furthermore in Bosnia and Herzegovina’s context tackling some of the reasons of insubstantial social cohesion. The key challenge concerning the subject is how to translate the concept into a practice that can effectively support necessarily development changes in Bosnia and Herzegovina for well-being of all citizens in this specific society.